High School Students' Health Literacy Related to the COVID-19 Pandemic in Indonesia - Astriningrum, Dita; Suwono, Hadi; Balqis, ‎; Dafip, Muchamad (KnE Social Sciences, 2024)
The global crisis due to COVID-19 demanded changes in people’s behavior to adapt to the pandemic. One factor that determined behaviors was literacy skills, especially in the health sector. A study related to the COVID-19 pandemic was carried out on high school students to assess students’ health literacy and determine related factors. Data collection was carried out from December 2021 to February 2022 by dividing urban areas, developing districts, and remote regions. The Health Literacy Questionnaire (HLQ) was adapted to suit the conditions of the COVID-19 pandemic. The data was interpreted as descriptive-narrative. Differences in literacy ability and the relationship with influencing factors were analyzed using ordinal regression and SEM-AMOS analysis. Limited health literacy was found in students from remote areas. A significant relationship was found between health literacy and class interest based on the ordinal regression test results. In contrast, health literacy was not related to gender, grade level, infected experience, and domicile. It was found that the ability to navigate health system information had a significant effect on students’ understanding of health literacy. Health literacy, which was low and unequal, is expected to improve strategic and sustainable education programs through science learning and physical health. Keywords: Health Literacy, COVID-19, Indonesia